Effect Of Herbicides On The Dynamics Of Culturable Soil Micro-Organisms In Groundnut - S. K. Sahoo; V.B. Kuruwanshi; B.Hota; M.Kar (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2016)
The present set of experiments was carried out in the Central farm, OUAT, Bhubaneswar during Rabi 2014-15. With five treatments such as control(without weeding), Butachlor, Alachlor, Oxyflurofen as pre-emergence herbicides and weed-free (manual weeding) having three replication under RBD design to The addition of herbicides can cause qualitative and quantitative alterations in the population of bacteria and fungi in the rhizospheric soil and their enzyme activities. All three herbicides were showing a drastic reduction in the bacterial as well as the fungal population within seven days after the application. An increasing trend of the bacterial and fungal population was observed after seven days and the trend continues up to 90 DAS. At 90 DAS the population of the bacteria and fungus became at par with the initial population i.e. 0 DAS. Among the control and the weed-free control, it was observed that the population of both the bacteria and the fungus is more in the weed-free control than the normal control. This could be due to the availability of more nutrients to the microbes due to weed-free conditions Application of pre-emergence herbicide affected the microflora population especially bacterial and fungal populations. The bacterial population was found to be highest ( 9x105 cfu/g ) in weed-free whereas on fungal population was highest ( 7x103 cfu/g) in the control treatment. The study confirmed that the herbicides (butachlor, alachlor, and oxyfluorfen) may alter the microbial populations with respect to different days after treatment, and thereby affects the different soil enzyme activities. Therefore, there is a need for the advent and use of cheaper, eco-friendly alternatives that result in increased crop production along with the judicious use of the known arsenal of agrochemicals as suggested by the integrated pest and nutrient management protocols.